11. INVESTIGATING THE STATUS OF HOSPITAL-ACQUIRED PNEUMONIA AND ANTIBIOTIC USAGE IN THE TREATMENT OF HOSPITAL-ACQUIRED PNEUMONIA AT THONG NHAT HOSPITAL (Vietnam Journal of Community Medicine, 2024)
Objective: The study aimed to assess the prevalence of Hospital-acquired pneumonia (HAP) and analyze the antibiotic usage in treating HAP at Thong Nhat Hospital.Subjects and Methods: A cross-sectional study was conducted, retrieving data from the medical records of inpatients treated at Thong Nhat Hospital in August 2023. Screening of medical records met the diagnostic criteria for HAP, including patients diagnosed with HAP by physicians or those diagnosed with pneumonia after at least 48 hours of hospitalization (satisfying the diagnostic criteria outlined in the 2016 Infectious Diseases Society of America/American Thoracic Society (IDSA/ATS) guidelines on the management of HAP and ventilator-associated pneumonia). A comparison of various indices, including treatment duration, medication costs, and antibiotic usage costs, was conducted between patient groups with and without HAP. Microbial analysis, antibiotic usage, and defined daily doses (DDD)/100 days of treatment were examined in patients with HAP.Results: The results from 2855 medical records revealed that there were 208 cases of HAP, accounting for 7.29%. The average age of patients with HAP was 72.65 years, with a male gender ratio of 55.77%. Patients with HAP had an extended treatment duration of approximately 7.35 days, resulting in a 2.7 times increase in treatment costs, a 10 times increase in medication costs, and a 25 times increase in antibiotic costs compared to patients without HAP. The mortality/severity rate in the healthcare-associated infection group was significantly higher compared to without HAP (22 times). The primary causative agents of HAP were Gram-negative bacteria, constituting 71.25%, including Klebsiella pneumonia (22.82%), Escherichia coli (16.78%), Pseudomonas aeruginosa (11.41%), and Acinetobacter baumannii (9.4%). Gram-positive bacteria accounted for 18.79%, with Staphylococcus being the highest at 16.78%. Fungi were also identified as causative agents, with a prevalence of 10.06%. The main antibiotics used for treatment were antibiotics group I, representing 50.33% of the total DDD per 100 days of treatment and constituting 80.88% of the antibiotic treatment costs.Conclusion: HAP is one of the common hospital-acquired infections. Patients with HAP often experience prolonged hospital stays, leading to increased treatment costs, decreased treatment effectiveness, and reduced quality of healthcare.
Keywords: Hospital-acquired pneumonia (VPBV); antibiotics